Investigations of Response Time Parameters of a Pneumatic 3/2 Direct Acting Solenoid Valve Under Various Working Pressure Conditions - Venkataraman, K. A.; Kanthavel, K.; Nirmal Kumar, B. (Engineering, Technology & Applied Science Research, 2013)
In pneumatic circuits, a solenoid valve is a key component for controlling and directing pneumatic energy. The solenoid valve functional performances are defined as response time parameters with respect to its actuations in terms of direction changing time. This paper aims to present response time parameters of solenoid valves under various working pressures. An experimental setup is employed in order to measure response time with reference to the input signals. The response time plays significant role for evaluating the valve performance in sensitive applications. The response time parameters includes the on delay, the off delay, the on time, the off time, the cycle time and the switching frequency. In this experimental investigation the influence of various input pressure conditions is recorded and tabulated. Valves with varying orifice diameter are employed and the investigation reveals the influence of orifice diameter in response time variations. The newly-proposed six response time parameters can be used to rate and select the appropriate valve for various industrial applications.